Impact of environmental knowledge toward green purchase intention: Attitude as mediator - Rahayu, Sri; Vedy, Nabila Kharimah; Novitasari, Evi (Department of Accounting, Faculty of Business, Universitas PGRI Yogyakarta, 2024)
Environmental knowledge and attitudes are important factors in increasing the purchase intention of environmentally friendly products. This study aims to analyze the influence of environmental knowledge on green buying intention through environmental attitudes as mediators. This research uses a quantitative approach. The population of this study is consumers of Tupperware's eco-friendly products in Bandar Lampung. The research sample is women aged 25 to 40 who have bought Tupperware products. The sampling technique uses a purposeful sampling technique, with the criteria of female samples, minimum age of 25 and maximum of 40 years, and domicile in Bandar Lampung City. The data of this study is sourced from primary data generated from the distribution of questionnaires. The data obtained was analyzed using SmartPLS. The results of this study show that environmental knowledge affects environmental attitudes and green buying intentions. Environmental attitudes can be a mediator between environmental knowledge and green buying intentions. It shows that environmental knowledge directly and indirectly affects green buying intentions, namely through environmental attitudes. does not have a significant direct influence on consumers' environmentally friendly purchase intentions.